Influences of Eastern Philosophy in Emerson’s Writings - Giri, Himal (Patan Pragya, 2020)
The paper explores and critically examines how the Vedic thought with specific reference to Brahma, the Bhagavad Gita, and the laws of Karma have influenced Ralph Waldo Emerson's prose works. The project shows an analysis of Emerson's works in relation to the Vedic philosophy. Therefore, criticisms and readings on his essays build up the background to illustrate the claim. The paper also demonstrates that there has been an impetus of Eastern philosophy on western writers including Ralph Waldo Emerson. The amalgam of Eastern philosophy and western vision beautifies the texture of this article. The readers will benefit from the knowledge of American transcendentalism.